When measure matters: Coresidence bias and intergenerational mobility revisited - Ercio Mu\~noz S.; Mariel Siravegna (Inter-American Development Bank (IDB), 2023)
We provide novel evidence of the impact of coresidence bias on a large set of indicators of intergenerational mobility in education. We begin re-examining a recent claim that the correlation coefficient is less biased than the regression coefficient. Then, we expand our analysis to show that there are indicators with varying average levels of coresidence bias going from less than 1% to more than 10%. However, some indicators with minimal bias produce high levels of re-ranking that make them uninformative to rank populations by the level of mobility. In contrast, other indicators with large bias generate more reliable rankings.
Keywords: D63; I24; J62; 330; Intergenerational mobility; Education; Coresidence bias; Truncation bias; Coresidency; Survey data; Census data